2015
DOI: 10.1002/2014jc010268
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on wave and surge processes in a Pacific Northwest (USA) estuary

Abstract: Total water levels (TWLs) within estuaries are influenced by tides, wind, offshore waves, and streamflow, all of which are uniquely affected by climate change. The magnitude of TWL associated with various return periods is relevant to understanding how the hydrodynamics of a bay or estuary may evolve under distinct climate scenarios. A methodology for assessing the hydrodynamic response of a small estuary under major boundary condition perturbations is presented in this study. The coupled Advanced Circulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
1
16
0
Order By: Relevance
“…The latter observation is expected since a best-fit conditional relationship between H s and T p was imposed. The findings are consistent with previous studies that have assessed changes in conditionally-derived extreme T p (e.g., Cheng et al, 2015).…”
Section: Projected Changes In Extreme Wave Conditions Along the Enp Csupporting
confidence: 92%
See 2 more Smart Citations
“…The latter observation is expected since a best-fit conditional relationship between H s and T p was imposed. The findings are consistent with previous studies that have assessed changes in conditionally-derived extreme T p (e.g., Cheng et al, 2015).…”
Section: Projected Changes In Extreme Wave Conditions Along the Enp Csupporting
confidence: 92%
“…All winds were available as 10 m neutrally-stable fields and similar to many previous studies (Cheng et al, 2015;Dobrynin et al, 2012), no bias adjustments were made. It is noted here that Graham et al (2013) found marked improvement when applying wind bias adjustments to CMIP3 wind fields.…”
Section: Gcm-simulated Near-surface Wind Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The studies in Table 3 are focused on, or explicitly give results for, tidal amplitude changes. It should be noted that there are many more studies (e.g., [8,13,49]) that consider a more holistic approach to changing extreme water elevations, of which tides are a component. Studies that do not explicitly provide information on the changes to tidal amplitudes are not included in Table 3.…”
Section: Modeling Studies Of Climate Change and Future Tidal Rangementioning
confidence: 99%
“…Small-scale regional hydrodynamic models are widely used to study many varied physical processes such as sediment transport [1][2][3]; storm surge inundation [4][5][6]; real-time surge forecast systems [7][8][9][10]; sea level rise [11][12][13][14]; passive fish and larval transport, as well as coupled ecological behavior [15][16][17]; combined hydrologic and hydrodynamic processes [9,18]; passive transport of oil spills [19] and coupled hydrodynamic-marsh interactions with biological feedback [20]. Each of these complex applications requires reliable tidal boundary forcing in order to provide accurate results.…”
Section: Introductionmentioning
confidence: 99%